Pengaruh Pengembangan Keprofesian dan Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Sekolah Dasar Negeri Se Kecamatan Serang - Fauziah; Andriani Sariwardini; Mutoharoh Mutoharoh (Journal of Innovative and Creativity, 2025)
This research aims to discover the effects of professional development and the principal leadership towards the teachers’ performance. This study is an expost facto study. The research sample consisted of 66 government employee teachers of Elementary School at Serang sub district was established using the simple random sampling technique. The data were collected by questionnaire. The data were analyzed using the descriptive analysis, regression analysis, and partial correlation analysis. The results of the study show that: 1) The professional development influences teacher’s performance by t hitung > t tabel which is 7,066 > 2,000 with coefficient determination is 43,8%, and coeffiecient partial correlation 0,597. 2) The principal leadership influences on teacher’s performance by t hitung > t tabel which is 3,811 > 2,000 with coeffiecient determination is 18,5%, and coeffiecient partial correlation 0,285. 3) The professional development and principal leadership influence teacher’s performance by F hitung > Ftabel or 28,568 > 3,13, and coeffiecient determination is 47,6%. It means the professional development after certification and motivation by their leadership influence the increase of teacher’s performance.in learning activities. Thus, the increasing of teacher’s performance can be efforted with the professional development after certification and the increasing of principal leadership fungtion.